Measuring the Effectiveness of Funding and Financing Products in Improving the Profitability of the Banking - Betari Putri Pavita; Vidya Purnamasari (JURNAL PENELITIAN EKONOMI DAN AKUNTANSI (JPENSI), 2022)
Sharia banks as financial institutions that run their business with Islamic principles have a role and contribution through the products and services provided to improve their performance. One of them is Bank Tabungan Negara, by channelling and withdrawing funds from the public, can improve the bank's health. This study aims to determine the effect of Tabungan Prima iB, Deposito BTN iB, KPR Sejahtera iB, and Multimanfaat iB on Return On Assets (ROA) at the Bank Tabungan Negara. This research method uses time-series data from 2018-2020 per month, with data analysis, namely multiple linear regression analysis through STATA software. The results showed that Prima iB Savings, KPR Sejahtera iB, and Multimanfaat BTN iB significantly affected BTN KCS Malang's profitability in 2018-2020. At the same time, the variable Deposits BTN iB has no significant effect on the Profitability of BTN KCS Malang in 2018-2020.